Analysis of Consumer Attitudes towards MSME-produced and Factory-produced Coffee Powder in East Java - Febriyanti Amirotul Nabila; Mardiyah Hayati (Universitas Muhammadiyah Malang, 2022)
The increasing trend of coffee consumption creates opportunities for business actors and coffee producers of various regions to produce MSME-made coffee powder as a competitor to the factory-made one. As the market competition becomes tougher, coffee powder producers need to equip themselves with the information on attributes useful to attract and maintain customers’ choice. The purpose of this study is to understand the characteristics of coffee powder consumers produced by both MSMEs and factories as well as to determine and analyze the level of importance, trust, and consumer attitudes. The sampling method used is accidental sampling with 100 respondents. As for the research methods, this research used descriptive and multi-attribute Fishbein analysis methods. The included attributes are taste, aroma, price, halal logo, packaging, coffee powder dregs, marketing place, and promotion. The results of the study informed that the characteristics of consumers are mostly aged 17-25 years old, male, working as students, residing in East Java, and having monthly income less than IDR 500,000. Consumer attitudes (Ao) towards MSMEs produced powder coffee is considered good by consumers.